Essentials of High Performance Water Electrolyzers - From Catalyst Layer Materials to Electrode Engineering - Pham, Chuyen Van; Escalera-Lopez, Daniel; Mayrhofer, Karl; Cherevko, Serhiy; Thiele, Simon (Advanced Energy Materials, 2021)
Proton-exchange membrane water electrolyzers (PEMWEs) will play a key role in future sustainable hydrogen production for mobility, households or chemical industry. Yet, the anode in PEMWEs, where the pivotal oxygen evolution reaction takes place, needs further improvement in terms of performance and cost. Both catalyst materials and electrode structure have to be optimized in order to inhibit degradation and reduce noble metal loadings. This review focuses on a holistic approach, covering all catalyst material, electrode structure, and transport layers within the framework of an overall electrode design, which not only optimizes the catalyst but also, all components of the electrode in conjunction. This review defines the goals for performance metrics of future PEMWEs in terms of power density and durability of the anode. Moreover, it summarizes manufacturing techniques and approaches that have a chance to be upscaled to meet the megawatt deployment of PEMWEs. The different aspects described jointly in this review such as novel catalyst system with higher intrinsic and structural performance or graded porous transport layers shall help to advance a next generation of electrodes.
CRIS-Team WoS Importer:2021-10-29